SENTIMENT ANALYSIS OF MANAGERIAL EFFECTIVENESS OF MSMEs (EMPIRICAL STUDY OF MSMEs IN CISAAT DISTRICT, SUKABUMI REGENCY) - Ajiz; Dana Budiman; Slamet Sutrisno (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the managerial effectiveness of Micro, Small, and Medium Enterprises (MSMEs) through a data mining-based sentiment analysis approach using Orange Data Mining software. This approach is used to examine the perceptions, experiences, and opinions of MSME actors regarding the implementation of managerial functions, which include strategic planning, organizing resources, directing and motivating, controlling and evaluating, and adapting to change. Research data was obtained through in-depth interviews with MSME actors, which were then processed using text mining techniques. The analysis process was carried out in several stages, namely text preprocessing, sentiment analysis using the VADER method, theme mapping with topic modeling based on the Latent Dirichlet Allocation (LDA) algorithm, and data visualization through word clouds, heat maps, and bar plots. The results show that the majority of respondents expressed positive sentiments towards the direction dimension, which reflects the ability of MSME managers to motivate team members. However, negative sentiments were also found regarding the control and adaptation dimensions to change, indicating a lack of consistency in evaluating and responding to market dynamics. This study confirms that the managerial effectiveness of MSMEs is not only determined by technical skills, but also by emotional intelligence, adaptive abilities, and leadership qualities in managing resources efficiently.